DA'WAH STRATEGY BIL HAL (DA'WAH WITH DEEDS) IN ISLAMIC EDUCATION INSTITUTIONS: A CASE STUDY OF ENTREPRENEURSHIP-BASED ISLAMIC BOARDING SCHOOLS - Moh. Affan; Malikul Habsi (As-Sulthan Journal of Education, 2025)
This study aims to analyze the supporting and inhibiting factors in managing pesantren financing based on Islamic entrepreneurship at Pondok Pesantren Al-Mashduqiah. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation, and then analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the supporting factors in pesantren financing management include the charismatic leadership of the kiai, strong community support, and the enthusiasm of santri in learning and entrepreneurship. Meanwhile, the inhibiting factors consist of limited capital, lack of experts in managing certain business units, and the low self-confidence of some santri in entrepreneurial practices. The study concludes that optimizing Islamic entrepreneurship management in pesantren requires strengthening capital, enhancing human resource capacity, and developing the entrepreneurial mindset of santri to ensure the sustainability of pesantren financing.